Marginal Consumers and Neoclassical Demand Theory - Novshek, William; Sonnenschein, Hugo (Journal of Political Economy, 1979)
We extend the neoclassical theory of demand so that marginal consumers play a significant role in the determination of the elasticity of aggregate demand. Price-induced demand changes are decomposed into three effects: an aggregate substitution effect, an aggregate income effect, and an aggregate change-of-commodity effect. The final effect measures the rate at which consumers switch consumption to a similar commodity when the price of the commodity which they are currently consuming rises. Theories of consumers who pick one unit of one type of a differentiated commodity as well as the neoclassical theory obtain as special cases.